REDESIGN ECO-FRIENDLY YOGURT PACKAGING USING KANSEI ENGINEERING METHOD - Hirawati Oemar; Hilda Farah Safira; Dewi Shofi Mulyati; Anis Saleh (Journal of Industrial Engineering Management, 2023)
This research is focused on the desire of companies to change their yogurt packaging from thin plastic pouches to stronger ones. The purpose of packaging redesign is not only to overcome the problem of packaging durability but also to make new packaging more attractive to consumers so that the selling value is higher. Thus, packaging that is technically feasible and represents the customer's preferences for the company's products is needed. In addition, companies must also consider the long-term environmental impact. Redesigning the packaging using the eco-design concept and the Kansei Engineering Method. Eco-design is used to determine the environmental impact of packaging, while Kansei Engineering is used as a product design tool. The eco-design assessment of the suggested packaging shows that the packaging is more environmentally friendly than the current packaging. Kansei Engineering's findings include cylinder-shaped yogurt packaging made from aseptic cardboard and full color with a packaging design that is fresh, cheap, beautiful, strong, environmentally friendly, ergonomic, complete with product information, a halal logo, and unique